Psychometric Properties of the Persian Version of Children's Active Play Imagery Questionnaire - Vali Ollah Kashani; Behroz Gol Mohamadi; Mansoureh Mokaberian (The Society of Aging and Physical Activity (SAPA), 2017)
Objectives. The purpose of this study was to determine the validity and reliability of the Persian version of the children's active play imagery questionnaire. Methods. For this purpose, 190 athletic children of the average age of 11.5 years were chosen through random sampling and they completed the Persian version of the children's active play imagery questionnaire (CAPIQ). At first, the data was confirmed with the use of back translation methods and check translation accuracy. Then, a confirmatory factor analysis, based on the structural equations model, was done to determine the constructive validity of the questionnaire. To determine its internal consistency, the Cronbach's alpha coefficient was used. The intra-class correlation coefficient (ICC) in the test-retest method was calculated to assess the temporal reliability of items. Results. The confirmatory factor analysis results suggested that the approximation square mean root was 0.07 and the comparative fit index was 0.94. Three factors and 11 items were properly verified in the questionnaire. The results of the Cronbach's alpha coefficient and the ICC showed that the CAPIQ has appropriate internal and temporal consistency in answers. Conclusion. Therefore, the Persian version of the CAPIQ can be regarded as a valid and reliable tool to be used by the researchers.